How Public Figures Use Language to Inspire: A Pragmatic Analysis of TED Talks by Book Writers and Its Implications for Effective Public Speaking Skills in the Digital Age - Anabella Nuryafitri; Otong Setiawan Djuharie (Indo Publishing, 2026)
This study examines how public figures who are primarily known as book authors use language pragmatically to inspire audiences in their TED Talks, and what implications these strategies hold for public speaking instruction in the digital age. Employing a qualitative descriptive design, the study analyzes the transcripts of five widely circulated TED Talks delivered by book writers: Brené Brown's